2015
DOI: 10.1090/tran/6369
|View full text |Cite
|
Sign up to set email alerts
|

The canonical trace and the noncommutative residue on the noncommutative torus

Abstract: Using a global symbol calculus for pseudodifferential operators on tori, we build a canonical trace on classical pseudodifferential operators on noncommutative tori in terms of a canonical discrete sum on the underlying toroidal symbols. We characterise the canonical trace on operators on the noncommutative torus as well as its underlying canonical discrete sum on symbols of fixed (resp. any) non-integer order. On the grounds of this uniqueness result, we prove that in the commutative setup, this canonical tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 34 publications
3
65
0
Order By: Relevance
“…Remark 5.4. Under the equivalence between our classes of ΨDOs and the classes of toroidal ΨDOs (see [31]) the above noncommutative residue agrees with the noncommutative residue for toroidal ΨDOs introduced in [38].…”
Section: Noncommutative Residuesupporting
confidence: 74%
“…Remark 5.4. Under the equivalence between our classes of ΨDOs and the classes of toroidal ΨDOs (see [31]) the above noncommutative residue agrees with the noncommutative residue for toroidal ΨDOs introduced in [38].…”
Section: Noncommutative Residuesupporting
confidence: 74%
“…defines a trace on the algebra of pseudodifferential operators [7,19], it follows from the uniqueness of traces on the algebra of pseudodifferential operators [18,15,25] that it coincides with the noncommutative residue defined in [15]. Therefore there exists a constant c such that for any P…”
Section: θ and Its Functional Relationsmentioning
confidence: 99%
“…For noncommutative four tori T 4 Θ , the scalar curvature is computed in [15] and it is shown that flat metrics are the critical points of the analog of the Einstein-Hilbert action. Also noncommutative residues for noncommutative tori were studied in [18,25,15] (see also [30]). We refer to [31,22] and [24] for detailed discussions on noncommutative residues for classical manifolds.…”
mentioning
confidence: 99%
“…As it has been shown [12] and more generally in [15] Wodzicki residue exists also in the case of the pseudodifferential calculus over noncommutative tori.…”
Section: Introductionmentioning
confidence: 82%
“…The symbol calculus defined in [4] and developed further in [3] (see also [15]) is easily generalised to the d-dimensional case and to the operators defined above. We shall briefly review the basic definitions and methods used further in the note.…”
Section: Pseudodifferential Operators On T D θmentioning
confidence: 99%